Things fall apart - Achebe, Chinua (London : Penguin Books, 2001)
Set in an Ibo village in Nigeria, the novel recreates pre-Christian tribal life and shows how the coming the white man led to the breaking up of the old ways.
Adult.
Adult
Keywords: Igbo (African people) -- Fiction; Men -- Nigeria -- Fiction; Igbo (African people) -- Fiction; Men -- Nigeria -- Fiction; Nigeria -- Race relations -- Fiction; Nigeria -- Race relations -- Fiction